Contemporary Family Dynamics: Online Ta'aruf Applications, Family Interventions, and Couple Interaction Crisis - Citra Az Zahraa; Meilany Hamdiah; Salma Salfira; Sri Damayanti (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
This study examines the dynamics of intimate relationships among Generation Z across three stages: partner selection through online ta’aruf platforms, family negotiation in wedding planning, and post-marital interactions that may lead to household disorganization. The aim of this study is to understand how individuals make relational decisions based on rational considerations. The method used is descriptive qualitative, with data collected through semi-structured interviews with purposively selected participants. Data analysis was conducted using a thematic approach grounded in Coleman’s Rational Choice Theory. The findings indicate that the use of online ta’aruf applications encourages more rational and structured partner selection while reducing physical commodification. In the wedding planning stage, there is a flexible negotiation process between individual autonomy and family expectations, resulting in mutually perceived fair compromises. Meanwhile, in the post-marital phase, low-quality interaction and lack of emotional presence, particularly in long-distance marriages, create vulnerability to infidelity, influenced by technological opportunities and weak social control. It is concluded that household disorganization emerges as an accumulative process rooted in interactional deficits. This study recommends strengthening relational communication and premarital preparation as preventive measures. Keywords: Partner Selection, Family Negotiation, Marital Interaction, Infidelity, Household Disorganization.